Peran Transformasi Kesadaran Kewargaan di Era Globalisasi Digital dalam Membangun Masyarakat Toleran: (Studi Kasus Respons terhadap Isu Rasisme di Media Sosial) - Salma Miftakhul Jannah; Peni Kunthi Hermawati; Heru Sujaryanto; Muhammad Hendri Nuryadi (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to explore how the transformation of civic consciousness in the digital era plays a role in shaping a more tolerant society, especially in responding to the issue of racism that is developing on social media. Using a qualitative approach through a case study method, this study analyzes various forms of digital citizen participation in dealing with discriminatory content. Data collection techniques were carried out through social media content analysis, literature review, and thematic interpretation based on two main theories, namely Digital Citizenship (Ribble, 2011) and Critical Consciousness (Freire, 1970). The results of the study found five main things: (1) the emergence of educational and emancipatory counter-narratives; (2) the transformation of individual expression into a collective movement through digital activism; (3) the important role of digital figures and alternative media in shaping tolerant public opinion; (4) the diversity of public responses, from progressive to regressive; and (5) structural challenges in the form of opinion polarization, the spread of disinformation, and the echo chamber effect. This study concludes that although social media is a complex and challenging space, it still has great potential as a vehicle for civic education and a tool for social transformation towards a society that values ​​diversity and upholds the values ​​of justice.